The impact of supply chain management practices on supply chain performance in Chinese manufacturing companies - Shufang, F. (Medwell Journals, 2016)
Supply Chain Management Practices (SCMP) and its positive effect on Supply Chain Performance (SCP) has been well addressed in manufacturing companies operating in developed industrial area. However, this association in manufacturing companies operating in developing industrial area is less emphasized. Therefore, this study aims to investigate the impact of SCMP on SCP for Chinese manufacturing companies in Lanzhou, the capital city of Gansu province, China. Based on the review of literature related to SCMP and SCP in developed industrial area, a conceptual model was established to determine the impact of SCMP on SCP for the companies. The model features five practices of SCMP - Customer-Supplier Relationship (CSR), Information Systems and Technology (IS/IT), Quality Management (QM), Corporate Culture (CC), Material Flow Management (MFM) and six items of SCP. A questionnaire was developed and distributed to all 156 manufacturing companies in Lanzhou. Analysis on the 112 completed questionnaires indicated that all the five SCMP are positively and significantly affect SCP. This means that, regardless of the state of industrial area, the SCMP were found to be important and have significant impact on SCP. This finding calls manufacturing companies in the developing industrial area to focus on SCMP to ensure the performance of supply chain management is sustained. Theoretical and managerial implication of the finding is discussed for measuring and improving the SCMP in manufacturing industry.